INOVASI IMPLEMENTASI KURIKULUM NASIONAL DAN KURIKULUM PONDOK PESANTREN MODERN DALAM PENINGKATAN AKHLAK SANTRI - Tajudin Tajudin; Muhajir Muhajir (QATHRUNÂ, 2019)
The objectives of this study are as follows; 1) To know the implementation of the National Curriculum at SMPIT Al-Ma'arif Ponpes Al-Qur'an Bany Salim; 2) To know the implementation of the Ponpes Curriculum at SMPIT Al-Ma'arif Ponpes Al-Qur'an Bany Salim; 3) To know the implementation of the integration of the National Curriculum and the Ponpes Curriculum at SMPIT Al-Ma'arif Ponpes Al-Qur'an Bany Salim in improving the morals of the students; 4) To determine the inhibiting and supporting factors in SMPIT Al-Ma'arif; This thesis research is included in field research, namely research activities carried out in a certain environment, in this case it will be conducted at SMPIT Al-Ma'arif Ponpes Al-quran Bany Salim. In this study, this research uses a qualitative approach with descriptive methods, where the researcher digs up data related to the Implementation of the National Curriculum and the Modern Islamic Boarding School Curriculum in Improving Santri Morals (Research in Integrated Islamic Junior High School (SMPIT Al-Ma'arif) Pondok Pesantren Al. -Qur'an Bany Salim Kramatwatu, Serang Regency) and describes the data in accordance with the research focus presented to clarify the purpose of the research. So the results of this study are for the implementation of the Islamic Boarding School Curriculum given the same face-to-face time as the National curriculum. In the past, the National Curriculum was put in the morning hours and the Pondok Curriculum was put in the afternoon hours, but now there is no difference in meaning between the Pesantren Curriculum and the National Curriculum being put together or random face-to-face hours. So if we discuss the school curriculum or curriculum at SMPIT Al-Ma'arif Bany Salim, there are 2 (two), the first is the national curriculum and the second is the boarding school curriculum set by the boarding school leader.